Synthesis and mechanical properties of TiC-Fe interpenetrating phase composites fabricated by infiltration process. Issue 17 (1st December 2018) - Zheng, Yong; Zhou, Yang; Feng, Yide; Teng, Xinyu; Yan, Shitao; Li, Runfeng; Yu, Wenbo; Huang, Zhenying; Li, Shibo; Li, Zhongwen
Abstract: TiC-Fe interpenetrating phase composites were fabricated by infiltrating molten iron into porous TiC preforms prepared by the organic template dipping method. The TiC-Fe interpenetrating phase composites exhibited a three-dimensional network structure, in which Fe and TiC phases interconnected with each other. The microstructures of porous TiC preforms and TiC-Fe interpenetrating phase composites were respectively characterized by SEM, and the phase compositions of preforms and composites were analyzed by XRD. No other amorphous phases were detected on the interface between TiC and Fe matrix, indicating that no reaction occurred between them. The Vickers hardness of a 4 vol% TiC (with Fe addition)-Fe interpenetrating phase composite increased gradually from 1.13 GPa for the pure Fe zone to 3.42 GPa for the TiC ceramic zone. The tensile strength of a 4 vol% TiC (with Mo addition)-Fe composite reached 343 MPa. The tensile fracture surfaces showed a strong interfacial bond between TiC and iron matrix. The TiC-Fe interpenetrating phase composites are more suitable for wear resistance applications as compared with Fe-matrix composites reinforced with discontinuous TiC particles.